Orchid biogeography and factors associated with rarity in a biodiversity hotspot, the Southwest Australian Floristic Region - Phillips, R.; Brown, A.; Dixon, Kingsley; Hopper, S. (2011)
Aim: The causes of orchid diversification and intrinsic rarity are poorly resolved. The Orchidaceae of the Southwest Australian Floristic Region use a diversity of pollination strategies and sites of mycorrhizal infection, and occupy a diversity of habitats. We combined a biogeographic analysis with analysis of factors associated with rarity to establish: (1) the landscape features correlated with taxon turnover and speciation, and (2) the possible role in taxon rarity of geographic region, pollination strategy, edaphic habitat and site of mycorrhizal infection. Location: Southwest Australian Floristic Region. Methods: The distributions of 407 orchid taxa (species and subspecies) were mapped at the quarter-degree scale using 13,267 collections in the Western Australian Herbarium. This database was used to map taxon richness, for a biogeographic analysis and to quantify rarity of taxa. Using herbarium records, rarity was expressed as mean abundance, mean distribution and incidence of rarity based on abundance and distribution for each genus. We tested for differences in rarity of species between pollination strategies, edaphic habitats and sites of mycorrhizal infection. Results: Taxon richness was highest in the High Rainfall Province. Biogeographic provincial boundaries for orchids were aligned with rainfall, while district boundaries tended to follow geological formations. When rarity was defined as either low abundance or small distribution, the greatest number of rare taxa occurred in areas of high taxon richness and naturally fragmented edaphic environments. For both abundance and distributional extent, sexual deception had a significantly higher incidence of rarity than food-rewarding taxa. There was no significant difference in rarity with site of mycorrhizal infection. Main conclusions: While large-scale edaphic and climatic variation are correlated with orchid taxon turnover and speciation in a similar fashion to the flora in general, the processes responsible for patterns of diversity may differ. Fragmented edaphic environments appear to be associated with a higher incidence of rare species due to limited dispersal/colonization opportunities or radiations of taxa in allopatry. The high incidence of rarity in sexually deceptive taxa could be due to either low fruit set or the risk of specializing on a single pollinator species.